Applying risk tolerance and socio-technical dynamics for more realistic energy transition pathways. (1st June 2021) - Cotterman, Turner; Small, Mitchell J.; Wilson, Stephen; Abdulla, Ahmed; Wong-Parodi, Gabrielle
Abstract: Many energy systems models have sought to develop pathways for deep decarbonization of the global energy system. Most often, these pathways minimize system costs or greenhouse gas emissions; with few exceptions, they ignore the constraints imposed by political, social, and economic factors that slow transition processes, making them prone to producing implausible decarbonization pathways. This paper integrates a key socio-technical factor—social acceptance of low-carbon nuclear power—into an energy systems model to illustrate how it alters the optimal energy generation mix. The United States was chosen as the example, but the approach itself is designed to be general and applicable to any region of interest. An empirically grounded risk tolerance model is developed to characterize acceptance of nuclear power and estimate an upper-bound deployment limit for the technology. Illustrative scenarios are presented to improve our understanding of how the socio-technical constraints that exist in the real world can alter deep decarbonization pathways. The cost-optimal generation portfolio to achieve net zero CO2 emissions by 2050 primarily relies on nuclear power. If risk tolerance concerns constrain nuclear deployment to socially acceptable levels, deep decarbonization scenarios are up to 11% more expensive than the reference scenario and require low-carbon options to be available and replace the reduced nuclear share. Results from this novel framework improve our representation of the effect of social acceptance on the adoption and diffusion of energy technologies. They also contribute to a growing literature that seeks to firmly embed the social sciences in climate and energy policy. Highlights: Plausible decarbonization pathways must also account for social constraints. We combine a social risk tolerance model with an energy system optimization model. We assess the role of social acceptance in constraining nuclear power's deployment. Social acceptance limits nuclear's share by as much as 71% in CO2 reduction pathways. Decision-making can be strengthened with integration of socio-technical analyses.